Conflict Resolution Strategy Based on Flight Conflict Network Optimal Dominating Set. (7th October 2022) - Wu, Minggong; Yang, Wenda; Bi, Kexin; Wen, Xiangxi; Li, Jianping
Abstract : Aiming at the problem that the air traffic flow is increasing year by year and the flight conflicts are difficult to be deployed, we take aircraft as the node and established a flight conflict network based on the flight conflict relationship between aircrafts. After that, we define the concept of an optimal dominating set. By removing the optimal dominating set nodes of the flight conflict network, the conflicts in the network can be quickly resolved and the complexity of the network is reduced. In the process of solving the optimal dominating set of the network, we introduce the immune mechanism based on the particle swarm algorithm (PSO) and ensure the priority deployment of a critical aircraft and high-risk conflicts by setting two types of antigens, nodes and connected edges. Compared with the traditional method, the conflict resolution strategy presented in this paper is able to quickly identify key aircraft nodes in the network and has better sensitivity to high-risk conflict edges, which can provide controllers and the control system with a more accurate and reliable suggestion to resolve the flight conflicts macroscopically.